Photocatalytic performance of granite waste in the decolorization and degradation of Reactive Orange 122. Issue 3 (June 2019) - Ferreira, S.A.D.; Donadia, J.F.; Gonçalves, G.R.; Teixeira, A.L.; Freitas, M.B.J. G.; Fernandes, A.A.R.; Lelis, M.F.F.
Abstract: The photocatalytic activity of granite waste (GW), an iron-rich material, was evaluated by the decolorization and degradation of Reactive Orange 122 (RO122) in the presence of H2 O2 by solar photo-Fenton. X-ray powder diffraction (XRD), 57 Fe Mössbauer spectroscopy, and scanning electron microscopy (SEM) confirmed the presence of magnetite (Fe3 O4 ), hematite (α-Fe2 O3 ), and zero-valent iron (α-Fe 0 ) in GW. GW showed great potential in the decolorization and degradation of RO122, reaching 100.0% efficiency at pH 3.0 and 91.0% efficiency at pH 6.5 under the best experimental condition (20 mg of waste and 3.0 mL of 0.040 mol L −1 H2 O2 ). The use of solar irradiation made the method more environmentally friendly and economic. RO122 degradation was best fitted to a first-order kinetic model ( k = 0.0684 min −1 for pH 3.0 and k = 0.0467 min −1 for pH 6.5). Dye solutions were completely decolorized and effectively mineralized, achieving a 68.7% total organic carbon (TOC) removal at pH 3.0 and a 29.2% TOC removal at pH 6.5. The results show that GW is a highly efficient heterogeneous photo-Fenton catalyst.